Optimal reprogramming factor stoichiometry increases colony numbers and affects molecular characteristics of murine induced pluripotent stem cells - Tiemann, Ulf; Sgodda, Malte; Warlich, Eva; Ballmaier, Matthias; Schöler, Hans R.; Schambach, Axel; Cantz, Tobias (Cytometry. Part A, 2011)
Somatic cells can be reprogrammed toward pluripotency by overexpression of a set of transcription factors, yielding induced pluripotent stem cells (iPSCs) with features similar to embryonic stem cells. Little is known to date about stoichiometric requirements of the individual reprogramming factors (RFs) for efficient reprogramming and especially about whether stoichiometry also influences the quality of derived iPSCs. To address this important issue, we chose bicistronic lentiviral vectors coexpressing fluorescent reporters (eGFP, dTomato, Cerulean, or Venus) along with the canonical RFs to transduce a bulk of murine embryonic fibroblasts (MEFs). Using a flow cytometric approach, we were able to independently and proportionally quantify all fluorophores in multiple‐infected MEFs and more importantly could sort these cells into all 16 stoichiometric combinations of high or moderate expression of the four factors. On average, we obtained about 600 alkaline phosphatase‐expressing colonies from 20,000 seeded cells. Interestingly, only seven different stoichiometric ratios gave rise to any colonies at all. The by far most colonies were obtained from those fractions, where Oct4 was in excess over the other three factors (2,386 colonies/20,000 cells), or where both Oct4 and c‐Myc were in excess over Sox2 and Klf4 (1,593 colonies/20,000 cells). Our findings suggest that increased Oct4 levels opposite to modest ones for Sox2 and Klf4 are required for satisfying reprogramming efficiencies and that these stoichiometries are also highly beneficial for achieving a stable pluripotent state independent of ectopic RF expression. Finally, the eligible Oct4high, Sox2low, and Klf4low subpopulation only resembles a small fraction of cells targeted by equal vector amounts, suggesting the necessity to address stoichiometry also in alternative approaches for iPSC generation or between different experimental systems. © 2011 International Society for Advancement of Cytometry.